PENERAPAN ANGGARAN BELANJA TERHADAP KINERJA OPERASIONAL DI DINAS PERTANIAN DAN PANGAN KOTA MAGELANG - Sulistyawati, Yenny Yakub; Khotijah, Siti Afidatul (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this research is to determine the implementation of the budget for operational performance in the Dinas Pertanian dan Pangan Kota Magelang. The research methods used in this study are qualitative analysis with a descriptive approach. The location of this research is Dinas Pertanian dan Pangan Kota Magelang. Data collection techniques are done with observation, and interviews. After the research, information and observation results can be concluded that in the mechanism of implementation of the budget in the Dinas Pertanian dan Pangan Kota Magelang, after ratified and approved into APBD then RKA converted to DPA. The budget to the operational performance in the Dinas Pertanian dan Pangan Kota Magelang makes a variety of activities that can be followed by the community so that it can be used wisely and help improve the welfare. In addition, there are several barriers to the implementation of activities programs, among others (1) that are unpredictable and out of planning as well; (2) There are limited human resources in the Dinas Pertanian dan Pangan Kota Magelang.